The integumentary ultrastructure of Cryptocellus bordoni Dumitresco and Jurvara-Bals, 1976 (Arachnida, Ricinulei) - Salvatierra, Lidianne; Tourinho, A. L. (Micron, 2016)
Ricinulei is an order of Arachnida composed of rare and little known species. The species of Ricinulei possess a rich variety of fine integumentary structures that have been poorly investigated in a few species. Besides, several structures are still undescribed and their function not yet addressed. In this paper we provide a detailed study of the integumentary morphology of Cryptocellus bordoni Dumitresco and Jurvara-Bals, 1976 using Light and Scanning Electron Microscopy. We describe and present photos of the new and already known fine integumentary structures. We compare the new structures to those previously described for other Ricinulei species and discuss their taxonomic implications and the placement of C. bordoni in the genus Cryptocellus. © 2015 Elsevier Ltd.
Keywords: Microscopy, Electron, Scanning; Taxonomies; Heteroricinoides; New World; Venezuela; Biological Materials Preservation; Anatomy And Histology; Animals; Arachnid; Integumentary System; Microscopy; Ultrastructure; Animal; Arachnida; Integumentary System; Microscopy